Quantitative study on the trade and ecological aspect of spice plants in the markets of District Bannu, Khyber Pakhtunkhwa, Pakistan - Ali Shah, Adnan; Badshah, Lal; Muhammad, Murad; Khan, Sumbal; Abbas, Muhammad; Abdullah; Khan, Naushad; Bussmann, Rainer W (Ethnobotany Research and Applications, 2021)
Background: This survey is the first extensive and large-scale spice plant assessment in four different spices marketplaces of district Bannu, Khyber Pakhtunkhwa, Pakistan. The study offers the first significant catalog of spice prices, the chain of collection, production, trade pattern and consumption. Methods: Consultation, personal observations, and group discussions with 90 informants (10% women and 90% male) using semi-structured questionnaires were conducted. Results: A total of 45 spice taxa belonging to 21 families were documented. The data were examined using various ethnoecological indices such as UV (Use Value), RFC (Relative Frequency of Citation), UR (Use Report), and CIV (Cultural Importance Value). Amongst all the taxa, the plant having the highest Use Value were Coriandrum sativum (0.783), used as Anti-cholesterol and carminative, Ocimum basilicum (0.742) for kidney problems, insomnia, and snake bites, and Piper nigrum (0.732) for cough. The UV ranged from 0.07 (Mangifera indica) to 0.78 (Coriandrum sativum). The most used spices plant parts were fruits (35.56%), trailed by seeds (28.89%), leaves (11.11%), bulb, bark, and rhizome (4.44%). RFC ranged from 0.16 (Mangifera indica) to (Coriandrum sativum) 0.82. The maximum RFC value was documented for Coriandrum sativum (0.822), trailed by Papaver somniferum (0.788), Cuminum cyminum, Ocimum basilicum, and Piper nigrum (0.777) each. Curcuma longa (0.65) had the maximum mCI (mean Cultural Importance) while the Mangifera indica (0.04) had the lowest. The majority off spice plants parts traded was imported (41 species, 91.11%) from India, China, Vietnam, Afghanistan, Iran, Brazil, and Nepal. Most of them were transported from Pakistan from different cities and provinces in Pakistan like Lahore, Karachi, Faisalabad, Gilgit, Peshawar, Quetta, and Multan into district Bannu. The minimum number of spice plants (8 species, 17.77%) were collected or cultivated locally. The spices plant having the highest trade price per kg (PKR 525000, US 3365) was Crocus sativus which is imported from Gilgit-Baltistan and China, while the lowest trade price was documented for Allium sativum (PKR 75, US 0.4) which is imported and also grown locally. Conclusions: The current study suggests that more detailed research would be highly interesting, as the district is well known for spices and medicinal plants. Keywords: Quantitative study, spices plants, spices markets, Bannu, Khyber Pakhtunkhwa, Pakistan.